Detection of milled 100Cr6 steel surface by eddy current and incremental permeance methods. (April 2017) - Perevertov, O.; Neslušan, M.; Stupakov, A.
Abstract: Hard milling was applied to 100Cr6 steel of 50 HRC hardness using cutting tools with different flank wear. The modified surface layers were investigated by eddy current and incremental permeance measurements at magnetizing frequencies from 0.2 to 10 kHz. The signals were studied as a function of a low-frequency magnetic field applied to the sample. Both methods showed growth of magnetically harder peak in the measured curve with tool flank wear and magnetizing frequency increase. New parameters were introduced to evaluate the flank wear and corresponding surface damage in the material. The incremental permeance method showed much higher sensitivity comparing to the eddy current testing. Graphical abstract: Highlights: Bearing steel was milled with the cutting tool flank wear from 0.05 to 0.8 mm. Modified surface was investigated by eddy currents and incremental permeance methods. Different excitation frequency was used from 0.2 to 10 kHz. The whole of the sample was additionally magnetized by a low-frequency field. The signals were studied as a function of that magnetic field.